Islamic Business Management and Sustainable Development Goals: A Conceptual Review for the Halal Economy (International Journal of Economics and Management Research, 2025)
This study aims to conceptually integrate the principles of Islamic Business Management (IBM) with the Sustainable Development Goals (SDGs) within the context of the global halal economy, emphasizing the importance of aligning Islamic ethical foundations with global sustainability agendas. Using a structured literature review approach, this study synthesizes scholarly contributions from the fields of Islamic management, sustainability, and halal industry studies to identify conceptual intersections and develop an integrative framework for sustainable halal business practices. The findings indicate that IBM, grounded in maqasid al-shari’ah, demonstrates a fundamental alignment with key SDG priorities, particularly in advancing social justice, inclusive economic growth, responsible consumption, and environmental preservation. The halal economy emerges as a practical and strategic domain in which these ethical values and global development objectives can be operationalized. This study contributes theoretically by bridging Islamic management discourse with contemporary sustainability frameworks and offers practical implications by providing guidance for policymakers, industry practitioners, and regulators in embedding sustainability principles within halal business ecosystems. By proposing a novel conceptual synthesis, this research positions the halal economy as an ethical, resilient, and sustainable model within the global marketplace.